A mulher Evangélica Congregacional em Angola Análise do processo da formação pastoral da mulher no período de 1965-1975 - Manuel, Adelaide Tomás (2005)
The aim of this project is to analyse the pastoral formation of women during 1965 to 1975, a period considered to be of great importance to the Church. The social, political, economic and religious contexts were analysed in order to present an overall idea of how the Congregational Evangelical Church was established in Angola. The presence of the first North American missionaries in the interior of the country as well as other episodes that occurred during the establishment of the Baliundo Church, which was considered the center of King Ekuikui II s kingdom in the early days of the Church, are presented. The development of the church, pastoral models, the cooperation of native peoples in the dissemination of the Gospel, the institutions of the Church, and the name change of the Church are given special attention. Relationships of genre, cultural formation, the pastoral formation of women, and the main courses given in missionary centers and in Dondi are discussed. The courses given included domestic economy, instruction in reading and writing, Christian and women s formation and delivery training instruction for midwives. The contribution of women to the development of the church and to the society was diversified, and continues until the present day. However, the work of lay women, the deaconess, minister s wives and their implementation of the Christian program merit special attention. The research also refers to the difficulties faced by women in the process of their formation, and the current situation of women s pastoral formation in Huambo and Angola as a whole. The present work proposes the pastoral formation of women as being capable of narrowing the gap between the old and the new generations